Metode Pendidikan dalam Surat An-Nahl Ayat 125 Perspektif Tafsir Al Mishbah - Azhari, Pebri; Fauzi, Sriyono (Lembaga Yasin AlSys, 2024)
Learning methods have a very important role in the field of educational methods because they aim to help teachers achieve certain targets or vision and mission that have been set or created by an educational institution. Educational methods will and will always develop following the times. As a guide for Muslims, the Qur'an provides many answers to many problems, especially in this case, namely educational methods. Tafsir Al Misbah written by Quraish Shihab provides various understandings from different points of view regarding the verses in the Al-Qur'an. This research aims to analyze the educational methods contained in Q.S An-Nahl 125 Based on Tafsir Al Misbah by Quraish Shihab. In this research, the researcher used the library research method. The findings from this research show that in verse 125 of Surah An-Nahl, according to Tafsir Al Misbah, there are three methods of Islamic education called hikmah, mau'idzah, and jidal.